Characteristics and outcomes of young patients with laryngeal cancer: National hospital‐based retrospective cohort analysis. Issue 10 (16th June 2022) - Yang, Alex; Tanamal, Priscilla; Tibbetts, Kathleen; Sumer, Baran; Blackwell, James‐Michael; Schostag, Kelly; Sher, David; Day, Andrew
Abstract: Background: The relative incidence of laryngeal cancer is rising in young patients, yet their characteristics, risk factors, and outcomes relative to older patients are poorly understood. Methods: Retrospective cohort analysis of the National Cancer Database from 2006 to 2015. Results: Among 25 029 total patients, 923 (3.7%) were young (<45 years old) and 3266 underwent tumor HPV testing. Compared to older patients, a greater proportion of young patients were female (30.3%, 23.3%; p < 0.001) and seen with high‐risk HPV‐positive tumors (29.9%, 12.4%; p < 0.001). In subset analyses of young patients, females with higher income (≥38 000) exhibited a decreased risk of overall mortality compared to all other sex‐income subcategories (adjusted hazard ratio [aHR]: 0.43, 95% confidence interval [CI]: 0.25–0.72). In subset analyses of patients of all ages with known tumor HPV status, patients with high‐risk HPV‐positive tumors exhibited a reduced risk of all‐cause mortality (aHR: 0.74, 95%CI: 0.60–0.92, p = 0.007). Conclusion: The interdependent associations between age, sex, tumor HPV status, and income on laryngeal cancer outcomes warrant further investigation.